Employee Teams' Readiness for Remote Work During The COVID-19 Pandemic - Katarzyna MIERZEJEWSKA; Michał CHOMICKI (Communications of International Proceedings, 2021)
The article discusses the concept of agile behavior, an example of which is the introduction of a remote work order during the COVID-19 pandemic. It also describes the history of popularizing remote work and presents different ways of perceiving it. The further part of the study presents the results of research on the polish employee teams' readiness for remote work. Research has shown that in times of the pandemic, employee teams from private enterprises do better than those from public enterprises, and those operating in enterprises with foreign capital than those with only Polish capital.
Keywords: COVID-19 Pandemic; Readiness for Remote Work; Employee Teams; Agile Behaviour.